2018
DOI: 10.1371/journal.pone.0202696
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of differentially expressed microRNAs and mRNAs in dorsal root ganglia from streptozotocin-induced diabetic rats

Abstract: Diabetic peripheral neuropathy is a common complication associated with diabetes mellitus with a pathogenesis that is incompletely understood. By regulating RNA silencing and post-transcriptional gene expression, microRNAs participate in various biological processes and human diseases. However, the relationship between microRNAs and the progress of diabetic peripheral neuropathy still lacks a thorough exploration. Here we used microarray microRNA and mRNA expression profiling to analyze the microRNAs and mRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The copyright holder for this preprint this version posted February 25, 2022. ; https://doi.org/10.1101/2022.02.24.481714 doi: bioRxiv preprint between patients with static or progressive diabetic neuropathy that are functionally enriched in pathways including the regulation of axonogenesis and lipid metabolism (Hur et al, 2011). A microarray analysis of the DRG of diabetic rats found that DEmRNAs with downregulated expression were significantly enriched in various biological processes, including myelination, peripheral nervous system myelination, axon guidance and regulation of axon production (Guo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted February 25, 2022. ; https://doi.org/10.1101/2022.02.24.481714 doi: bioRxiv preprint between patients with static or progressive diabetic neuropathy that are functionally enriched in pathways including the regulation of axonogenesis and lipid metabolism (Hur et al, 2011). A microarray analysis of the DRG of diabetic rats found that DEmRNAs with downregulated expression were significantly enriched in various biological processes, including myelination, peripheral nervous system myelination, axon guidance and regulation of axon production (Guo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified hundreds of differentially expressed genes between patients with static or progressive diabetic neuropathy that are functionally enriched in pathways including the regulation of axonogenesis and lipid metabolism(Hur et al, 2011). A microarray analysis of the DRG of diabetic rats found that DEmRNAs with downregulated expression were significantly enriched in various biological processes, including myelination, peripheral nervous system myelination, axon guidance and regulation of axon production(Guo et al, 2018). Aberrantly expressed mRNAs in SCs isolated from the sciatic nerve of diabetic rats were enriched in downregulated biological processes related to myelination, axonogenesis and axon development(Wang et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al examined microRNA and mRNA expression profiling in the dorsal root ganglia isolated from diabetic rats and built a microRNA-gene network. They found that miR-17-1-3p, miR-330-5p, and miR-346 are potent promoters of DN (113). Xourgia et al proposed that miR-146, miR-499a, and miR-199a-3p are possible biomarkers of DN (21).…”
Section: Mirnas As Biomarkers In the Diagnosis Of Diabetic Neuropathymentioning
confidence: 99%
“…In another microarray analysis of miRNAs in DRG tissues of DPN rats, 37 miRNAs were differentially expressed in the diabetic group. Specifically, 15 and 22 miRNAs were upregulated or downregulated, respectively [60]. In particular, using a miRanda database, 10,011 predicted target genes were found from the 37 dysregulated miRNAs; a miRNA-gene-network analysis revealed that among these miRNAs, miR-330-5p, miR-17-1- 3p, and miR-346 had a high degree of correlation [60].…”
Section: Micrornas and Diabetic Neuropathymentioning
confidence: 99%
“…Specifically, 15 and 22 miRNAs were upregulated or downregulated, respectively [60]. In particular, using a miRanda database, 10,011 predicted target genes were found from the 37 dysregulated miRNAs; a miRNA-gene-network analysis revealed that among these miRNAs, miR-330-5p, miR-17-1- 3p, and miR-346 had a high degree of correlation [60]. Meanwhile, podocalyxin-like (Podxl, inhibiting cell-cell adhesion) and homeobox A1 (Hoxa1, sequence specific transcription factor) were the most common target mRNAs with the highest degrees of connectivity [60].…”
Section: Micrornas and Diabetic Neuropathymentioning
confidence: 99%